Composite resin, preparation method and application thereof, and dental prosthesis

The composite resin prepared by hot pressing of multi-layer materials, combined with inorganic nanofillers and composite antibacterial agents, solves the problem of insufficient wear resistance and antibacterial properties of dental resin materials, achieves high hardness, excellent antibacterial properties and color gradient effects, and improves the service life and aesthetic effect of dentures.

CN119795708APending Publication Date: 2025-04-11AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411985520.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing dental resin materials have poor wear resistance in denture repair, are prone to shrinkage and lead to micro leakage, and the single color cannot meet the aesthetic effect of the gradient of natural teeth color.

Method used

Multi-layer materials are used to prepare composite resin by hot pressing, and the color is deepened in sequence from top to bottom. The color difference between the two adjacent layers is <1, and the color difference between the uppermost and lowermost layers is >4. At the same time, inorganic nanofiller is added to the upper half to improve hardness, and composite antibacterial agent is added to the lower half to improve antibacterial ability.

Benefits of technology

It improves the wear resistance and antibacterial properties of dentures, extends the service life of dentures, enhances the repair success rate, and achieves the aesthetic effect of color gradient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795708A_ABST
    Figure CN119795708A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of dental materials, in particular to composite resin, a preparation method and application thereof and a dental prosthesis. According to the composite resin provided by the invention, the upper half part (cutting end) has high hardness, so that a false tooth can be endowed with good wear resistance, and the service life of the false tooth is prolonged; the lower half part (the neck end) has excellent antibacterial ability, so that diseases such as secondary caries and periodontitis caused by bacterial aggregation can be avoided, and the success rate of denture repair is increased; meanwhile, the colors of the composite resin are deepened in sequence, the color difference value of the two adjacent layers of materials is smaller than 1, the color difference value of the uppermost layer and the lowermost layer of materials is larger than 4, the characteristic of color gradual change is shown, and the good aesthetic effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dental materials, and in particular to a composite resin, a preparation method and application thereof, and a dental restoration. Background Art

[0002] As the population ages, the demand for denture restoration is also increasing. However, the wear resistance of existing dental resin materials for dentures is poor, which affects the service life of the dentures. In addition, during the process of denture restoration, due to the easy shrinkage of dental resin materials, micro-leakage is easily formed between the teeth, and cracks and other phenomena may occur during wearing, causing bacteria to gather and cause secondary caries and periodontitis, which requires replacement of the restoration for treatment, resulting in restoration failure.

[0003] Furthermore, the composite resin materials used in existing dental restorations are mostly single-color, and the dentures produced are all the same color. Compared with natural teeth, they have the disadvantage of low color similarity and cannot meet the aesthetic effect of the color gradient of natural teeth. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a composite resin and its preparation method and application, and a dental restoration. The composite resin has high hardness and excellent antibacterial ability, while taking into account mechanical and aesthetic properties, which helps to improve the service life of dentures and the success rate of restoration.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a composite resin obtained by hot pressing multiple layers of materials; the color of the composite resin gradually deepens from top to bottom, and the color difference between two adjacent layers of materials is less than 1, and the color difference between the uppermost layer and the lowermost layer of materials is greater than 4;

[0007] The composite resin consists of an upper half and a lower half;

[0008] The hardness of the upper part of the composite resin is ≥28HV1;

[0009] The antibacterial rate of the lower part of the composite resin against Streptococcus mutans is ≥90%.

[0010] Preferably, in terms of mass percentage, each layer of material in the upper half of the composite resin independently comprises 64-84.99% of the first resin, 0.01-1% of the first colorant and 15-35% of the inorganic nanofiller;

[0011] Calculated by mass percentage, each layer of material in the lower half of the composite resin independently includes 89-98.99% of the second resin, 0.01-1% of the second colorant and 1-10% of the composite antibacterial agent.

[0012] Preferably, in terms of mass percentage, the first resin and the second resin independently include 10-100% of polymer material and 0-90% of monomer.

[0013] Preferably, the polymer material comprises 97-99.9% of polymer and 0.1-3% of initiator in terms of mass percentage.

[0014] Preferably, the initiator is a peroxide initiator.

[0015] Preferably, the polymer comprises polymethacrylate;

[0016] The monomers include one or more of methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane, 2,2-bis[4-(acryloxy-ethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-ethoxy)phenyl]propane, carbamate di(meth)acrylate, and 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diol dimethacrylate.

[0017] Preferably, the polymethacrylate includes one or more of polymethyl methacrylate, polyethyl methacrylate, polypropyl methacrylate, polyn-butyl methacrylate, polyisobutyl methacrylate and polyhexyl methacrylate;

[0018] The methacrylate includes one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate and 2-phenoxyethyl methacrylate.

[0019] Preferably, the inorganic nanofiller includes one or more of nano silicon oxide, nano aluminum oxide, nano zinc oxide, nano titanium oxide and nano zirconium oxide.

[0020] Preferably, the composite antibacterial agent includes a nano-metal oxide antibacterial agent and an organic antibacterial agent.

[0021] Preferably, the nano metal oxide antibacterial agent includes one or more of nano zinc oxide, nano silver oxide, nano yttrium oxide, nano lanthanum oxide, nano magnesium oxide, nano copper oxide, nano aluminum oxide and nano iron oxide;

[0022] The organic antimicrobial agent includes one or more of methacryloyloxydodecylpyridinium bromide, 2-methacryloyloxyethyl phosphorylcholine, polyethyleneimine, quaternary ammonium methacrylate, polyhexamethyleneguanidine hydrochloride and polyhexamethylene biguanide hydrochloride.

[0023] Preferably, the first colorant and the second colorant independently include one or more of zirconium vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, iron oxide red, erbium oxide, titanium dioxide, cobalt oxide, chromium oxide, iron oxide brown, iron oxide black and carbon black.

[0024] Preferably, the upper part includes at least 2 layers of material, the lower part includes at least 2 layers of material, and the number of material layers in the lower part is ≥ the number of material layers in the upper part.

[0025] The present invention provides a method for preparing the composite resin of the above scheme, comprising the following steps: mixing the raw materials corresponding to each layer to obtain materials for each layer;

[0026] The materials of each layer are laid in sequence as required and then hot pressed to obtain the composite resin.

[0027] Preferably, the hot pressing temperature is 108-180° C., the pressure is ≤20 MPa, and the time is ≥15 min.

[0028] The present invention provides the use of the composite resin described in the above scheme or the composite resin prepared by the preparation method described in the above scheme in preparing a dental restoration.

[0029] The present invention provides a dental restoration, comprising the composite resin described in the above scheme or the composite resin prepared by the preparation method described in the above scheme.

[0030] Preferably, the dental restoration comprises one or more of an inlay, an onlay, a single crown and a triple bridge.

[0031] The present invention provides a composite resin obtained by hot pressing multiple layers of materials; from top to bottom, the color of the composite resin deepens successively, and the color difference value of the adjacent two layers of materials is less than 1, and the color difference value of the uppermost and lowermost layers of materials is greater than 4; the composite resin is composed of an upper half and a lower half; the hardness of the upper half of the composite resin is ≥28HV1; the antibacterial rate of the lower half of the composite resin against Streptococcus mutans is ≥90%. The composite resin provided by the present invention has high hardness in the upper half (cut end), which can give the denture good wear resistance and improve the service life of the denture; the lower half (neck end) has excellent antibacterial ability, which can avoid bacteria aggregation causing secondary caries and periodontitis and other diseases, and improve the success rate of denture repair; at the same time, the color of the composite resin deepens successively, and the color difference value of the adjacent two layers of materials is less than 1, and the color difference value of the uppermost and lowermost layers of materials is greater than 4, showing the characteristics of color gradient, and having a good aesthetic effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 and Figure 2 This is a photo of the composite resin prepared in Example 1. DETAILED DESCRIPTION

[0033] The present invention provides a composite resin obtained by hot pressing multiple layers of materials; the color of the composite resin gradually deepens from top to bottom, and the color difference between two adjacent layers of materials is less than 1, and the color difference between the uppermost layer and the lowermost layer of materials is greater than 4;

[0034] The composite resin consists of an upper half and a lower half;

[0035] The hardness of the upper part of the composite resin is ≥28HV1;

[0036] The antibacterial rate of the lower part of the composite resin against Streptococcus mutans is ≥90%.

[0037] In the present invention, the thickness of each layer of material is preferably the same.

[0038] The upper part of the composite resin will be described below.

[0039] In the present invention, the upper part comprises at least two layers of material.

[0040] In the present invention, in terms of mass percentage, each layer of material in the upper half of the composite resin independently comprises 64-84.99% of the first resin, 0.01-1% of the first colorant and 15-35% of the inorganic nano filler.

[0041] In a specific embodiment, the mass content of the first resin in each layer of material in the upper half of the composite resin can be 64%, 68%, 72%, 75%, 78%, 80%, 82% or 84.99%; the content of the first colorant can be 0.01%, 0.03%, 0.05%, 0.07% or 1%; the content of the inorganic nanofiller can be 15%, 20%, 25%, 30% or 35%.

[0042] In the present invention, the resin matrix preferably includes 10-100% of polymer material and 0-90% of monomer in terms of mass percentage. In a specific embodiment, the content of polymer material in the resin matrix can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%, and the balance is monomer.

[0043] In the present invention, the polymer material preferably includes 97-99.9% of polymer and 0.1-3% of initiator in terms of mass percentage; in a specific embodiment, the content of polymer in the polymer material can be 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or 99.9%, and the content of initiator can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%.

[0044] In the present invention, the polymer preferably includes polymethacrylate; the polymethacrylate preferably includes one or more of polymethyl methacrylate, polyethyl methacrylate, polypropyl methacrylate, polyn-butyl methacrylate, polyisobutyl methacrylate and polyhexyl methacrylate. In the present invention, the weight average molecular weight of the polymethacrylate is preferably 300,000 to 900,000, and in specific embodiments, it can be 300,000, 400,000, 500,000, 600,000, 700,000, 800,000 or 900,000.

[0045] In the present invention, the monomer preferably includes one or more of methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane, 2,2-bis[4-(acryloxy-ethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-ethoxy)phenyl]propane, carbamate di(meth)acrylate and 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diol dimethacrylate; the methacrylate preferably includes one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate and 2-phenoxyethyl methacrylate.

[0046] In the present invention, the initiator is preferably a peroxide initiator; the peroxide initiator preferably includes one or more of benzoyl peroxide, tert-butyl peracetate, diisopropylbenzene peroxide, tert-butyl peroxy-2-ethylhexanoate and tert-butyl perbenzoate.

[0047] In the present invention, the first colorant preferably includes one or more of zirconium vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, iron oxide red, erbium oxide, titanium dioxide, cobalt oxide, chromium oxide, iron oxide brown, iron oxide black and carbon black.

[0048] In the present invention, the inorganic nanofiller preferably includes one or more of nano silicon oxide, nano aluminum oxide, nano zinc oxide, nano titanium oxide and nano zirconium oxide. In the present invention, the inorganic nanofiller functions to improve the hardness and wear resistance of the upper part of the composite resin.

[0049] Calculated by mass percentage, each layer of material in the lower half of the composite resin independently includes 89-98.99% of the second resin, 0.01-1% of the second colorant and 1-10% of the composite antibacterial agent.

[0050] Next, the lower half of the composite resin will be described.

[0051] In the present invention, the lower part includes at least 2 layers of material, and the number of material layers in the lower part is greater than or equal to the number of material layers in the upper part.

[0052] Calculated by mass percentage, each layer of material in the lower half of the composite resin independently includes 89-98.99% of the second resin, 0.01-1% of the second colorant and 1-10% of the composite antibacterial agent.

[0053] In a specific embodiment, the mass content of the second resin in each layer of material in the lower half of the composite resin can be 89%, 90%, 92%, 94%, 96%, 98% or 98.99%; the content of the second colorant can be 0.01%, 0.03%, 0.05%, 0.07% or 1%; the content of the composite antibacterial agent can be 1%, 3%, 5%, 7% or 10%.

[0054] In the present invention, the type of the second resin is preferably the same as that of the first resin; the type of the second colorant is preferably the same as that of the first colorant, which will not be described in detail here.

[0055] In the present invention, the composite antibacterial agent preferably includes a nano metal oxide antibacterial agent and an organic antibacterial agent; the nano metal oxide antibacterial agent preferably includes one or more of nano zinc oxide, nano silver oxide, nano yttrium oxide, nano lanthanum oxide, nano magnesium oxide, nano copper oxide, nano aluminum oxide and nano iron oxide; the organic antibacterial agent preferably includes one or more of methacryloyloxydodecylpyridinium bromide, 2-methacryloyloxyethyl phosphorylcholine, polyethyleneimine, quaternary ammonium methacrylate, polyhexamethyleneguanidine hydrochloride and polyhexamethylene biguanide hydrochloride.

[0056] In the present invention, the function of the composite antibacterial agent is to impart good antibacterial properties to the lower part of the composite resin, thereby improving the success rate of denture restoration.

[0057] The present invention adopts a composite antibacterial agent to inhibit the proliferation of bacteria and free bacteria on the surface of the composite resin material while ensuring the mechanical properties and aesthetics of the original resin material.

[0058] In the present invention, the thicknesses of the layers of material in the upper and lower parts of the composite resin are preferably the same.

[0059] In the present invention, the total thickness of the composite resin is preferably 10 to 50 mm, and in a specific embodiment, it can be 10 mm, 20 mm, 30 mm, 40 mm or 50 mm.

[0060] The present invention provides a method for preparing the composite resin of the above scheme, comprising the following steps: mixing the raw materials corresponding to each layer to obtain materials for each layer;

[0061] The materials of each layer are laid in sequence as required and then hot pressed to obtain the composite resin.

[0062] In a specific embodiment, the first resin, the first colorant and the inorganic nanofiller are mixed to obtain the layers of material in the upper half; the second resin, the second colorant and the composite antibacterial agent are mixed to obtain the layers of material in the lower half; and then the materials are laid in sequence according to the color difference value requirements and then hot-pressed to obtain the composite resin.

[0063] In the present invention, the temperature of the hot pressing is preferably 108-180°C, the pressure is preferably ≤20MPa, more preferably 2-20MPa, and the time is preferably ≥15min. In a specific embodiment, the temperature of the hot pressing can be 108°C, 120°C, 140°C, 150°C, 160°C or 180°C; the pressure of the hot pressing can be 2MPa, 5MPa, 10MPa, 15MPa or 20MPa.

[0064] The present invention provides the use of the composite resin described in the above scheme or the composite resin prepared by the preparation method described in the above technical scheme in preparing dental restorations.

[0065] The present invention provides a dental restoration, comprising the composite resin described in the above scheme or the composite resin prepared by the preparation method described in the above technical scheme.

[0066] In the present invention, the dental restoration preferably comprises one or more of an inlay, an onlay, a single crown and a triple bridge.

[0067] The composite resin provided by the present invention, its preparation method and application, and dental restoration are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0068] Example 1

[0069] This embodiment provides a composite resin material for dentistry, and the preparation method is as follows:

[0070] Example 1 is prepared from 6 layers of material, each layer of material has the same thickness, and the total thickness is 30 cm, wherein the first to third layers are the upper half, and the fourth to sixth layers are the lower half. The composition of each component in each layer of material is shown in Table 1.

[0071] Table 1 Composition of each layer of material in Example 1

[0072]

[0073]

[0074] The resin in Table 1 is polymethyl methacrylate (weight average molecular weight of 600,000) and initiator benzoyl peroxide (BPO), wherein the mass of the initiator accounts for 2% of the mass of the resin. The resin, colorant, inorganic filler and composite antibacterial agent are mixed evenly according to the percentage content in Table 1 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the chromaticity value from low to high to obtain a multi-layer material; the mold is heated to 160° C., and the obtained multi-layer material is hot-pressed at a pressure of 10 MPa for a holding time of 1.5 h; after cooling, the mold is removed to obtain a composite resin with a gradient color (as shown in the actual picture). Figure 1 and Figure 2 As shown, you can see the color gradient effect).

[0075] Example 2

[0076] This embodiment provides a composite resin material for dentistry, and the preparation method is as follows:

[0077] Example 2 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 2.

[0078] Table 2 Composition of each layer of material in Example 2

[0079]

[0080] The resin in Table 2 is a composition of a polymer material and methyl methacrylate, wherein the mass ratio of the polymer material to the methyl methacrylate in the resin is 0.60:0.40, and the polymer material is composed of 98% polymethyl methacrylate (weight average molecular weight of 550,000) and 2% initiator BPO. The resin, colorant, inorganic filler and composite antibacterial agent are uniformly mixed according to the percentage content in Table 2 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the chromaticity value from low to high to obtain a multilayer material; the mold is heated to 130° C., and the obtained multilayer material is hot-pressed at a pressure of 2.5 MPa for a holding time of 15 min; the mold is removed after cooling to obtain a composite resin with a gradient color.

[0081] Example 3

[0082] This embodiment provides a composite resin material for dentistry, and the preparation method is as follows:

[0083] Example 3 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 3.

[0084] Table 3 Composition of each layer of material in Example 3

[0085]

[0086] The resin in Table 3 is a composition of a polymer material and methyl methacrylate, wherein the mass ratio of the polymer material to the methyl methacrylate in the resin is 0.67:0.33, and the polymer material is composed of 98% polymethyl methacrylate (weight average molecular weight of 500,000) and 2% initiator BPO. The resin, colorant, inorganic filler and composite antibacterial agent are uniformly mixed according to the percentage content in Table 3 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the chromaticity value from low to high to obtain a multilayer material; the mold is heated to 135° C., and the obtained multilayer material is hot-pressed at a pressure of 2.5 MPa for a holding time of 20 min; the mold is removed after cooling to obtain a composite resin with a gradient color.

[0087] Example 4

[0088] This embodiment provides a composite resin material for dentistry, and the preparation method is as follows:

[0089] Example 4 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 4.

[0090] Table 4 Composition of each layer of material in Example 4

[0091]

[0092] The resin in Table 4 is a polymer material and butyl methacrylate composition, the mass ratio of the polymer material to butyl methacrylate in the resin is 0.75:0.25, the polymer material is composed of 97% polyethyl methacrylate (weight average molecular weight of 300,000) and 3% initiator diisopropylbenzene peroxide (DCP), the raw materials are mixed evenly according to the percentage content in Table 4 to make each layer of material with different chromaticity; each layer of material is sequentially molded according to the transmittance to obtain a multilayer material; the mold is heated to 145°C, and the obtained multilayer material is hot-pressed at a pressure of 5MPa for a holding time of 30min. After cooling, the mold is removed to obtain a composite resin with a gradient color.

[0093] Example 5

[0094] This embodiment provides a composite resin material for dentistry, and the preparation method is as follows:

[0095] Example 5 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 5.

[0096] Table 5 Composition of each layer of material in Example 5

[0097]

[0098] The resin in Table 5 is a polymer material and butyl methacrylate composition, the mass ratio of the polymer material to butyl methacrylate in the resin is 0.80:0.20, and the polymer material is composed of 97% polyethyl methacrylate (weight average molecular weight of 250,000) and 3% initiator tert-butyl hydroperoxide (TBHP); the raw materials are mixed evenly according to the percentage content in Table 5 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the transmittance to obtain a multi-layer material; the mold is heated to 150°C, and the obtained multi-layer material is hot-pressed at a pressure of 7.5MPa and a holding time of 40min. After cooling, the mold is removed to obtain a composite resin with a gradient color.

[0099] Comparative Example 1

[0100] The composite resin material of Comparative Example 1 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 6.

[0101] Table 6 Composition of each layer of material in Comparative Example 1

[0102]

[0103]

[0104] The resin in Table 6 is polymethyl methacrylate (weight average molecular weight of 550,000) and initiator BPO, wherein the mass of the initiator is 2% of the mass of the resin. The raw materials are mixed evenly according to the percentage in Table 6 to prepare each layer of material with different chromaticity; each layer of material is put into the mold in turn to obtain a multilayer material; the mold is heated to 155°C, and the obtained multilayer material is hot-pressed at a pressure of 5MPa for a holding time of 2h; the mold is removed after cooling to obtain a resin with a gradient color.

[0105] Comparative Example 2

[0106] The composite resin material of Comparative Example 2 is prepared from 6 layers of materials, and the composition of each component in each layer of material is shown in Table 7.

[0107] Table 7 Composition of each layer of material in Comparative Example 2

[0108] Number of layers Resin, % Titanium dioxide, % Red iron oxide, % Iron oxide yellow, % Iron oxide black, % First floor 99.936423 0.059965 0.000942 0.002623 0.000047 Second floor 99.936780 0.059965 0.000853 0.002358 0.000044 Third floor 99.937092 0.059965 0.000810 0.002092 0.000041 Fourth floor 99.937403 0.059965 0.000768 0.001826 0.000038 Fifth floor 99.933217 0.059965 0.000725 0.005977 0.000116 Sixth floor 99.934028 0.059965 0.000682 0.005218 0.000107

[0109] The resin in Table 7 is a composition of a polymer material and methyl methacrylate, wherein the mass ratio of the polymer material to the methyl methacrylate in the resin is 0.67:0.33, and the polymer material is composed of 98% of polymethyl methacrylate (weight average molecular weight of 500,000) and 2% of initiator BPO; the raw materials are uniformly mixed according to the percentage content in Table 7 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the chromaticity value from low to high to obtain a multilayer material; the mold is heated to 135° C., and the obtained multilayer material is hot-pressed at a pressure of 2.5 MPa for a holding time of 20 min; the mold is removed after cooling to obtain a composite resin with a gradient color.

[0110] Comparative Example 3

[0111] The composite resin material of Comparative Example 3 is prepared from 6 layers of materials, and the composition of each component in each layer of materials is shown in Table 8.

[0112] Table 8 Composition of each layer of material in Comparative Example 3

[0113]

[0114]

[0115] The resin in Table 8 is a composition of a polymer material and butyl methacrylate, wherein the mass ratio of the polymer material to butyl methacrylate in the resin is 0.75:0.25, and the polymer material is composed of 97% polyethyl methacrylate (weight average molecular weight of 300,000) and 3% initiator DCP; the raw materials are uniformly mixed according to the percentage content in Table 8 to prepare each layer of material with different chromaticity; each layer of material is sequentially molded according to the transmittance to obtain a multilayer material; the mold is heated to 145° C., and the obtained multilayer material is hot-pressed at a pressure of 5 MPa for a holding time of 30 min; the mold is removed after cooling to obtain a composite resin with a gradient color.

[0116] Analytical Testing

[0117] The color gradient composite resins prepared in Examples 1 to 2 and Comparative Examples 1 to 2 were tested, and the test methods and standards were as follows:

[0118] The antibacterial rate of the lower part of the composite resin material prepared in each embodiment and comparative example against Streptococcus mutans was tested with reference to the standard "GB / T 31402-2015 Test method for antibacterial performance of plastic surface"; the flexural strength and elastic modulus of the composite resin material were tested with a Shimadzu universal tensile testing machine with reference to the standard "YY0710-2009 Polymer-based crown and bridge materials for dentistry"; the hardness of the upper part of the composite resin material was tested with a Vickers hardness tester;

[0119] The chromaticity value is tested by a spectrophotometer, the light source is "D65", the measurement mode is "reflection" and "SCI", and the chromaticity measurement value is obtained, and the chromaticity measurement value includes L*, a* and b* values. The calculation formula of the chromaticity difference between two adjacent layers (referred to as "color difference value") is formula 1:

[0120]

[0121] In formula 1, L*, a* and b* values ​​are the measured values ​​of chromaticity, and n is the material of the nth layer; the specific results are shown in Table 9;

[0122] The obtained composite resin was cut into samples with a size of Φ(22±0.1) mm×(2.1±0.01) mm, and the cutting marks were removed by grinding with 400-grit sandpaper, and then the sample was water-ground with 2000-grit sandpaper until the thickness of the sample was 2.00±0.01 mm.

[0123] The test results are summarized in Table 9.

[0124] Table 9 Test results of Examples 1 to 3 and Comparative Examples 1 to 3

[0125]

[0126]

[0127]

[0128] As can be seen from Table 9, the color difference between two adjacent layers of Examples 1 to 3 ranges from 0.24 to 0.99, all less than 1.0, and the color difference from the first layer to the last layer is greater than 4, so that the resins prepared in Examples 1 to 3 have a natural color transition, and the cut teeth also have a color gradient effect, which has a high aesthetic effect. At the same time, the antibacterial rates of Examples 1 to 3 against Streptococcus mutans are all greater than 90%, which is an excellent antibacterial rate compared to Comparative Examples 1 to 3. After adding inorganic fillers, the hardness of Examples 1 to 3 is increased.

[0129] In Comparative Example 1, since the color difference between the first and last layers is less than 4, the color change of the teeth from one end to the other cannot be achieved. In Comparative Example 2, the color difference between the first and second layers is 1.17, and the color difference between the second and third layers is 1.10, which causes color stratification between layers and unnatural color transition. In Comparative Example 3, the color difference between the first and last layers is small (less than 4), and the color gradient effect is poor. In addition, since Comparative Examples 1 to 3 do not use antibacterial agents and inorganic fillers, the antibacterial rates against Streptococcus mutans are all less than 25%, and the antibacterial effects are poor; the hardness is less than 28.

[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite resin, characterized in that: It is obtained by hot pressing multiple layers of materials; from top to bottom, the color of the composite resin gradually deepens, and the color difference between two adjacent layers of materials is less than 1, and the color difference between the uppermost layer and the lowermost layer of materials is greater than 4; The composite resin consists of an upper half and a lower half; The hardness of the upper part of the composite resin is ≥28HV1; The antibacterial rate of the lower part of the composite resin against Streptococcus mutans is ≥90%.

2. The composite resin according to claim 1, characterized in that Calculated by mass percentage, the materials of each layer of the upper half of the composite resin independently include 64-84.99% of the first resin, 0.01-1% of the first colorant and 15-35% of the inorganic nano filler; Calculated by mass percentage, each layer of material in the lower half of the composite resin independently includes 89-98.99% of the second resin, 0.01-1% of the second colorant and 1-10% of the composite antibacterial agent.

3. The composite resin according to claim 2, characterized in that Calculated by mass percentage, the first resin and the second resin independently include 10-100% of polymer material and 0-90% of monomer.

4. The composite resin according to claim 3, characterized in that Calculated by mass percentage, the polymer material comprises 97-99.9% of polymer and 0.1-3% of initiator.

5. The composite resin according to claim 4, characterized in that The initiator is a peroxide initiator.

6. The composite resin according to claim 4, characterized in that The polymer comprises polymethacrylate; The monomers include one or more of methacrylate, ethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, 2,2-bis[4-(2-hydroxy-3-methacryloxypropoxy)phenyl]propane, 2,2-bis[4-(acryloxy-ethoxy)phenyl]propane, 2,2-bis[4-(methacryloxy-ethoxy)phenyl]propane, carbamate di(meth)acrylate, and 4,13-dioxo-3,14-dioxa-5,12-diazahexadecane-1,16-diol dimethacrylate.

7. The composite resin according to claim 6, characterized in that The polymethacrylate includes one or more of polymethyl methacrylate, polyethyl methacrylate, polypropyl methacrylate, polyn-butyl methacrylate, polyisobutyl methacrylate and polyhexyl methacrylate; The methacrylate includes one or more of methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate and 2-phenoxyethyl methacrylate.

8. The composite resin according to claim 2, characterized in that The inorganic nano filler includes one or more of nano silicon oxide, nano aluminum oxide, nano zinc oxide, nano titanium oxide and nano zirconium oxide.

9. The composite resin according to claim 2, characterized in that The composite antibacterial agent comprises a nano metal oxide antibacterial agent and an organic antibacterial agent.

10. The composite resin according to claim 9, characterized in that The nano metal oxide antibacterial agent includes one or more of nano zinc oxide, nano silver oxide, nano yttrium oxide, nano lanthanum oxide, nano magnesium oxide, nano copper oxide, nano aluminum oxide and nano iron oxide; The organic antimicrobial agent includes one or more of methacryloyloxydodecylpyridinium bromide, 2-methacryloyloxyethyl phosphorylcholine, polyethyleneimine, quaternary ammonium methacrylate, polyhexamethyleneguanidine hydrochloride and polyhexamethylene biguanide hydrochloride.

11. The composite resin according to claim 2, characterized in that The first colorant and the second colorant independently include one or more of zirconium vanadium yellow, cerium praseodymium yellow, lemon yellow, iron oxide yellow, chrome yellow, iron oxide red, erbium oxide, titanium dioxide, cobalt oxide, chromium oxide, iron oxide brown, iron oxide black and carbon black.

12. The composite resin according to any one of claims 1 to 11, characterized in that The upper part includes at least 2 layers of material, the lower part includes at least 2 layers of material, and the number of material layers in the lower part is greater than the number of material layers in the upper part.

13. The method for preparing the composite resin according to any one of claims 1 to 12, characterized in that: The method comprises the following steps: mixing the raw materials corresponding to each layer to obtain materials for each layer; The materials of each layer are laid in sequence as required and then hot pressed to obtain the composite resin.

14. The preparation method according to claim 13, characterized in that: The temperature of the hot pressing is 108-180° C., the pressure is ≤20 MPa, and the time is ≥15 min.

15. Use of the composite resin according to any one of claims 1 to 12 or the composite resin prepared by the preparation method according to any one of claims 13 to 14 in preparing dental restorations.

16. A dental restoration, characterized in that: A composite resin comprising the composite resin according to any one of claims 1 to 12 or a composite resin produced by the production method according to any one of claims 13 to 14.

17. The dental restoration according to claim 16, characterized in that The dental restoration comprises one or more of an inlay, an onlay, a single crown and a triple bridge.

Citation Information

Patent Citations

  • Dental crown composite material for implant denture and preparation method of dental crown composite material

    CN114191315A

  • Bionic composite material for dental restoration and application thereof

    CN115350335A

  • Resin with gradually changed color and light transmittance, preparation method and application thereof, and artificial tooth simulating natural tooth

    CN119174706A